A monoclonal antibody toolkit for C. elegans. - Gayla Hadwiger; Scott Dour; Swathi Arur; Paul Fox; Michael L Nonet (PLoS ONE, 2010)
Antibodies are critical tools in many avenues of biological research. Though antibodies can be produced in the research laboratory setting, most research labs working with vertebrates avail themselves of the wide array of commercially available reagents. By contrast, few such reagents are available for work with model organisms.We report the production of monoclonal antibodies directed against a wide range of proteins that label specific subcellular and cellular components, and macromolecular complexes. Antibodies were made to synaptobrevin (SNB-1), a component of synaptic vesicles; to Rim (UNC-10), a protein localized to synaptic active zones; to transforming acidic coiled-coil protein (TAC-1), a component of centrosomes; to CENP-C (HCP-4), which in worms labels the entire length of their holocentric chromosomes; to ORC2 (ORC-2), a subunit of the DNA origin replication complex; to the nucleolar phosphoprotein NOPP140 (DAO-5); to the nuclear envelope protein lamin (LMN-1); to EHD1 (RME-1) a marker for recycling endosomes; to caveolin (CAV-1), a marker for caveolae; to the cytochrome P450 (CYP-33E1), a resident of the endoplasmic reticulum; to beta-1,3-glucuronyltransferase (SQV-8) that labels the Golgi; to a chaperonin (HSP-60) targeted to mitochondria; to LAMP (LMP-1), a resident protein of lysosomes; to the alpha subunit of the 20S subcomplex (PAS-7) of the 26S proteasome; to dynamin (DYN-1) and to the alpha-subunit of the adaptor complex 2 (APA-2) as markers for sites of clathrin-mediated endocytosis; to the MAGUK, protein disks large (DLG-1) and cadherin (HMR-1), both of which label adherens junctions; to a cytoskeletal linker of the ezrin-radixin-moesin family (ERM-1), which localized to apical membranes; to an ERBIN family protein (LET-413) which localizes to the basolateral membrane of epithelial cells and to an adhesion molecule (SAX-7) which localizes to the plasma membrane at cell-cell contacts. In addition to working in whole mount immunocytochemistry, most of these antibodies work on western blots and thus should be of use for biochemical fractionation studies.We have produced a set of monoclonal antibodies to subcellular components of the nematode C. elegans for the research community. These reagents are being made available through the Developmental Studies Hybridoma Bank (DSHB).